The Ramat Bet Shemesh Regional Project: Landscapes of Settlement From the Paleolithic to the Ottoman Periods - Yehuda Dagan (Israel Antiquities Authority, 2011)
The Ramat Bet Shemesh Regional Project: Landscapes of Settlement from various periods.